RADEN JONO: BANYUMAS FABEL (EDUCATIONAL CHARACTER ANALYSIS) - Muh Nurul Huda; Sumarlam Sumarlam; Kundharu Saddhono (Universitas Sebelas Maret, 2017)
The aim of this research is to analyze the character value from one of Banyumas fables entitled Raden Jono.The analysis content to be used is based on Eriyanto and Rakhmat’s. The data is Banyumas fable text, that is on Panginyongan modul from Javanese Teachers’ MGMPof Banyumas regency.The analysis of the text is focused on the educational character value by which it is showed on the result of this researchdiscussion in the form of text quotations.The resultof this research shows that there are educational character (abbreviated EC) as values in this fable by which it can be able to be appliedin the daily life as it affects the positivities in our life to influence good attitude and gain our spirit up.